HERLeadership: Addressing the Continued Lack of Women in Leadership (Journal of Leadership, Accountability and Ethics, 2021)
In this conceptual paper, we argue for theory adaptation of the K-12 educational leadership framework in Ontario, Canada. We propose that leadership characteristics, skills, values and behaviours for women and equity-seeking groups differ from traditional white, male-oriented leadership expectations. As an illustrative example, one recent study of women principal’s experiences in leadership in one school district in Ontario is discussed. We further compared leadership behaviours of women from three different studies and found that authentic school leadership differs from the current leadership expectations that are identified and valued in Ontario. Leadership frameworks that are devoid of anti-racist, anti-oppression concepts and language fail to challenge norms and address concerns about power, discrimination, ethics, and organizational politics. Without addressing identity in leadership, organizational equity, diversity and inclusion strategies remain performative, create barriers, and possibly exacerbate gender and racial disparities.
Keywords: leadership; accountability; ethics; K-12 education; feminism; gender; race; identity; equity